PENGARUH MEDIA COUNTING HANDS TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK ANANDA DESA PADAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Ardianza, Elsa; Risma, Devi; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of Counting Hands media on the ability to recognize the symbol of numbers in children aged 4-5 years in Ananda’s Kindergarten, Pandau Jaya Village, Subdistrick Siak Hulu, Kampar District. This research uses experimental method with pretest posttest control design research group design. The population in this study were children aged 4-5 years, amounting to 46 children and the sample used is 46 children divided into two classes, experimental class and control class. The data collection technique used is observation. Data analysis technique used t-test with SPSS 23 program. The hypothesis of the research is the influence of the use of Counting Hands media to the ability to recognize the symbol of the number of children aged 4-5 years in Ananda’s Kindergarten, Pandau Jaya Village, Subdistrick Siak Hulu, Kampar District. This can be known from the analysis of pretest and posttest comparison of experimental class obtained thitung= 18,097 and sig. (2-tailed)= 0.000. Because sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is the influence of the ability to recognize the symbol of a very significant number after using the media Counting Hands at the time of learning. In the hypothesis test can be seen thitung = 18,097 > ttabel = 2,073. So it means Ho is rejected and Ha accepted meaningful in this research there is influence of Counting Hands media before and after to the ability to recognize the symbol of the number of children in the experimental class. The influence of Counting Hands media on the ability to recognize the symbol of the number of children in the experimental class. The influence of Counting Hands media on the ability to recognize the symbol of the number of children aged 4-5 years in Ananda’s Kindergarten, Pandau Jaya Village, Subdistrick Siak Hulu, Kampar District by 44%.Keywords: Ability to recognize the symbol of number, Counting Hands Media, SPSS